Care for the spiritual dimension provided by caregivers in a nursing home - Lucivalda Barbosa Santos; Tânia Maria de Oliva Menezes; Raniele Araújo de Freitas; Marta Gabriele Santos Sales; Ana Luíza Barreto de Oliveira; Amélia Maria Pithon Borges Nunes (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand care for the spiritual dimension provided by caregivers in a Nursing Home. Methods: this is a qualitative research, carried out in a geriatric center of a philanthropic hospital in the city of Salvador, Bahia. Eighteen formal caregivers participated, through a semi-structured interview, between January and February 2019. The data were analyzed in the light of Jean Watson’s Theory of Transpersonal Caring. Results: formal caregivers discuss the spiritual dimension based on older adults’ religious beliefs, encourage religious practices and exercise spiritual care according to older adults’ physical, emotional and spiritual demands. Final Considerations: formal caregivers understand that older adults’ religious or spiritual experiences should be included in their work routine. Care for the spiritual dimension occurs by stimulating faith in God, encouraging religious practices and embracing their beliefs in the face of physical, emotional and spiritual demands.